Clustering potential of organized industrial zones in Turkiye - Sakarya, Adem (SPRINGERNATURE, 2023)
This article analyzes the clustering potentials of organized industrial zones (OIZs) in Turkiye. Studies related to cluster identification first identify the related industries and then analyze the spatial agglomerations of the related industries. To define the clustering potential of OIZs, first the related industries are identified using an input-output table showing the inter-industry trade relations and a formula is suggested to calculate the clustering potential coefficient. This coefficient is an original contribution to the literature. Also, this study is the first to analyze all OIZs in Turkiye using clustering potentials. Of the 347 organized industrial zones in Turkiye, 193 were analyzed. The results show the OIZs are agglomerated in specific regions and the OIZs located in populous and industrialized regions have higher occupancy rates. Also, OIZs clustering potential varies with production type. Specialized OIZs have a greater potential than mixed OIZs. Also, OIZs with greater clustering potential do not agglomerate but are spread across the country.
Keywords: Industrial clustering; Clustering identification; Clustering potential coefficient; Organized industrial zones; Turkiye; MANUFACTURING-INDUSTRY; IDENTIFICATION; AGGLOMERATION; INNOVATION; COMPLEXES; NETWORKS; SPACE; Business & Economics; Environmental Sciences & Ecology; Public Administration